Creep Effect and Prediction Method of Dynamic Disaster of Surrounding Rock - Wen, Zhijie; Tao, Jian.; Song, Zhenqi; Zuo, Yujun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book provides a comprehensive overview of the author$1 (Bs in-depth insights into the theory, prediction methods, and developmental trends of creep instability and failure in coal-rock masses within mining stopes. The content primarily covers topics such as creep instability of coal-rock masses in stopes, creep instability of surrounding rock in roadways, large-scale roof creep instability, creep instability of overlying strata in goaf, rockburst, gas outburst, and principles and prediction of roof creep instability in fully mechanized mining faces. Additionally, it explores theoretical advancements in analyzing the energy principles of coal-rock masses and acoustic wave monitoring of coal-rock systems. This book serves as a valuable reference for professionals and researchers in mining engineering, mine construction, underground space engineering, and geotechnical engineering, as well as for faculty and students in related fields.s
Principles and Prediction of Creep Instability in Coal-Rock Masses -- Principles and Prediction of Creep in Roadway Surrounding Rock -- Principles and Prediction of Large-Scale Roof Weighting in Mining Faces -- Principles of Creep in Overlying Strata of Goaf and Mine Seismic Prediction -- Principles and Prediction of Coal-Rock Burst -- Principles and Prediction Methods for Coal Seam Gas Outbursts -- Principles of Roof Weighting and Creep Instability in Fully Mechanized Mining Faces -- Energy Principle Analysis of Coal-Rock Masses -- Mine Pressure Monitoring Technology and Applications -- Principles and Applications of Acoustic Wave Monitoring in Coal-Rock Masses.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Engineering geology; Geoengineering